Conservative Treatment for Right Ventricular Free Wall Rupture in a Patient with Acute Myocardial Infarction - Mohd Al-Baqlish Mohd Firdaus; Nur Syahirah Abdul Rahim; Nurtasneem Rusdi; Nor Saadah Idris; Mohd Ridzuan Mohd Said; Imran Zainal Abidin (Case Reports in Cardiology)
Ventricular wall rupture possesses a high mortality rate in patients with acute myocardial infarction. We presented a case of a ninety-year-old gentleman who presented with acute inferolateral myocardial infarction in cardiogenic shock and right ventricular free wall rupture. He was treated conservatively and survived.